Midwifery Care for Pregnant Women with Atopic Dermatitis - Finta isti kundarti; Nurul Mulkil Aliyah; Ira Titisari; Didien Ika Setyarini (KHD Production, 2025)
Atopic dermatitis, or atopic eczema, is a chronic inflammatory skin disease characterized by itchy red skin lesions, xerosis, ichthyosis, and skin pain. Among the social impacts of atopic dermatitis are difficulty and isolation in relationships and social stigmatization. In addition, atopic dermatitis is known to cause sleep disturbances, anxiety, hyperactivity, and depression. This study aims to provide midwifery care in cases of atopic dermatitis experienced by pregnant women in the third trimester. The case study design in this study uses an in-depth approach to the subjective mother A, age 31 years, G3P1011, gestational age 32-33 weeks, who comes with complaints of itching on the body with skin conditions experiencing dryness and scaling, which causes the skin surface to feel rough. Data was collected through interviews, observation, physical examination, and documentation study. The examination was carried out through inspection and palpation of the skin area experiencing complaints, along with an assessment of the skin condition. Interviews regarding the history of allergies and precipitating factors reinforced the initial diagnosis. The diagnosis made was atopic dermatitis in pregnant women in the third trimester with complaints of pruritic and dry skin. Midwifery interventions were carried out through observation and education. Evaluation results showed a decrease in itching complaints and improved skin condition. This study emphasizes the importance of early detection of skin dryness and a holistic approach in supporting the comfort and skin health of pregnant women.